2023
DOI: 10.3390/s23031278
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and Quantification of Upper Body Surface Motions for Tidal Volume Determination in Lung-Healthy Individuals

Abstract: Measurement of accurate tidal volumes based on respiration-induced surface movements of the upper body would be valuable in clinical and sports monitoring applications, but most current methods lack the precision, ease of use, or cost effectiveness required for wide-scale uptake. In this paper, the theoretical ability of different sensors, such as inertial measurement units, strain gauges, or circumference measurement devices to determine tidal volumes were investigated, scrutinised and evaluated. Sixteen subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Hence, there remains a need for alternative methods for measuring respiratory volumes using upper body surface motion. A previous study [3] has shown that upper body movements are in some cases highly correlated with changes in respiratory volumes. This fact can be utilized for the determination of respiratory volumes via upper body movements, and some current approaches used inertial measurement units [18][19][20], others used strain gauges [21,22] or optical encoder systems, as in belts measuring changes in circumferences [23][24][25].…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Hence, there remains a need for alternative methods for measuring respiratory volumes using upper body surface motion. A previous study [3] has shown that upper body movements are in some cases highly correlated with changes in respiratory volumes. This fact can be utilized for the determination of respiratory volumes via upper body movements, and some current approaches used inertial measurement units [18][19][20], others used strain gauges [21,22] or optical encoder systems, as in belts measuring changes in circumferences [23][24][25].…”
Section: Introductionmentioning
confidence: 88%
“…The study was based on the data recorded in Laufer et al [3], where a motion capture system (MoCap) (Bonita, VICON, Denver, CO, USA) with nine infrared cameras (VICON Bonita B10, firmware version 404) was used to measure the respiratory-induced movements of the human upper body via 102 highly reflective motion capture markers, attached at precise locations on a compression shirt. A schematic of the measurement system is shown in Figure 1.…”
Section: Measurement Setupmentioning
confidence: 99%
See 3 more Smart Citations